Strategies and skills of managing small and medium businesses - Mamyrbayev, A. N. (Journal of Economic Research & Business Administration, 2015)
In this article, the strategies and skills necessary for managing small and medium organizations are considered. In the first part of the article, the general widely used strategy and instruments of running business are described. In particular, the author analyzes such strategies and instruments as “Ansoff Matrix”, philosophy of management “Kaizen”, personal characteristics that shall be possessed by an entrepreneur. Further, the distinctions between strategies of managing large businesses in comparison with small ones are discussed. The author concludes that there are significant differences between the management of large and small companies and not in all cases the large business has advantage over small business. Finally, the skills and strategies necessary for successful running small and medium business are reviewed.